National Policies and the Challenge of Coherence - Andabaka, Ana; Basarac Sertić, Martina; Yiatros, Stylianos; Nisiforou, Olympia A.; De Simone, Marilena; Tambovceva, Tatjana; Atstāja, Dzintra; Cudečka-Purina, Natālija; Borg, Ruben Paul; Iordachi, Victoria; Muntean, Neli; Trombeva Gavriloska, Ana; et al. (My University, 2026)
This chapter explores the complexities of aligning national policies with the European Union’s objectives in transitioning to a circular economy within the construction sector. While EU directives establish general frameworks, national governments encounter challenges in adapting these directives into coherent and context-specific regulations. The chapter identifies key obstacles to effective policy implementation, including fragmentation, institutional overlap, and inconsistent terminology. Additionally, it examines how governance structures, planning traditions, and institutional cultures influence policy coherence. The analysis is based on survey results collected in 2023. Although subsequent policy and regulatory changes have occurred in the past two years, the data remain relevant, as they capture the main trends and challenges that continue to shape national approaches to circular construction. By analyzing case studies and examples from various member states, the chapter emphasizes the necessity for enhanced multilevel coordination, harmonized regulatory frameworks, and knowledge-sharing platforms. Bolstering policy coherence is crucial to ensure that national initiatives make meaningful contributions to the EU’s circular economy goals and the broader sustainability agenda.
Keywords: Construction; circular economy